Efeito da associação de Panax ginseng (ginseng vermelho) e Angelica keskei (ashibata) e da fotobiomodulação nos parâmetros cardiovasculares encontrados em ratas ovariectomizadas - Silva, Nayara Formenton (2024)
Menopause is a natural, age-related physiological process that results in a decrease in the production of steroid hormones, mainly estrogen, which can affect systems and organs and lead to hypertension. Complementary therapeutic strategies have been gaining prominence as an option for the safe management of menopausal women, such as herbal medicines and photobiomodulation. The combination of Panax ginseng (red ginseng) + Angelica keiskei (ashitaba) (Pg +Ak) is a formulation that can improve vascular function and photobiomodulation (PBM) consists of the use of light, in the wavelength range between 400 and 1300nm, in body tissues. Objectives: The objective of this work was to evaluate the in vivo effects of herbal medicines and photobiomodulation on cardiovascular parameters in menopause induced by ovariectomy in rats. Methods: Fifty-two Wistar rats, 70 days old, were randomly distributed into six experimental groups, sham (SH), ovariectomized (OVX), ovariectomized treated with Panax ginseng + Angelica keiskei (OVX+Pg+Ak) and ovariectomized treated with photobiomodulation (OVX+PBM). All animals in the OVX groups had their ovaries removed in the 12th week of life. The animals in the group treated with herbal medicines received 100 mg/kg/day for two weeks intraperitoneally. The animals in the group treated with photobiomodulation received energy 5.6 Joules per point, at 6 application points in the abdominal region, with a power of 100mW, twice a week, for two weeks, at 660nm. Blood pressure and endothelial function parameters were evaluated in all animals by tail plethysmography and vascular reactivity, respectively. Results: At the end of treatments, mean arterial pressure in the treated groups decreased compared to the untreated group. Endothelial function was impaired in aortic rings from OVX rats compared to Sham. Treatment with Pg+Ak and PBM improved endothelium-dependent vasodilation in the animals' aortic rings, as well as NO concentration. Conclusion: Our results suggest that the combination of Panax ginseng + Angelica keiskei was able to reduce blood pressure levels and reverse endothelial dysfunction in ovariectomized rats, as well as treatment with photobiomodulation.